Susceptibility of Haemophilus influenzae Isolates from Blood and Cerebrospinal Fluid to Ampicillin, Chloramphenicol, and Trimethoprim-Sulfamethoxazole - McGowan, John E. (1976)
Susceptibility to ampicillin and chloramphenicol in vitro has been determined for Haemophilus influenzae strains isolated from blood and/or cerebrospinal fluid cultures of patients admitted to two Atlanta hospitals from 1 January 1974 to 31 March 1975. Since the appearance of ampicillin-resistant strains of this organism in early 1974, chloramphenicol has been used in these hospitals as initial therapy for severe infection due to H. influenzae. Strains from five of 94 patients were resistant to ampicillin (minimum inhibitory concentration [MIC] ≥ 12.5 μg/ml), but all strains were susceptible to chloramphenicol (MIC < 2 μg/ml). The first 35 strains studied, including three resistant to ampicillin, were also tested for in vitro susceptibility to trimethoprim-sulfamethoxazole; all were highly susceptible (MIC ≤ 0.0312 μg of trimethoprim and 0.625 μg of sulfamethoxazole per ml).